Positioning Analysis of Online Transportation Companies in Indonesia Based on Marketing Mix Aspects - Waliyul Arinni, Rizqoni; Manshur Ali Suyanto, Achmad (International Journal of Scientific Research and Management (IJSRM), 2023)
Technology disruption has brought significant changes in various aspects of life, including transportation systems. The growth of online transportation companies in Indonesia is dynamic, there are four top brands chosen for online transportation services in Indonesia, including Gojek, Grab, Maxim, and inDrive. The advent of online transportation has brought numerous positive impacts as well as challenges, including intense competition among online transportation companies. Professional positioning is one such effective and efficient strategy for competition. Therefore, this study aims to conduct an analysis of the positioning of online transportation companies in Indonesia based on marketing mix aspects. The research method employed in this study is quantitative, and questionnaire was used as the research instrument with 400 sample size. The data analysis technique used in this research is descriptive analysis, which includes crosstabulation, mean, and multidimensional scaling analysis. The results of this research show a positioning map that describes the positioning and competitive map of online transportation companies in Indonesia. Gojek and Grab are in the same quadrant, quadrant I. Maxim and inDrive are also in the same quadrant too, quadrant III. This indicates that Gojek and Grab as well as Maxim and inDrive are perceived to have many similarities in terms of their indicators, making their competition appear head-to-head. The result is Gojek is the most superior online transportation company among others in every aspect of the marketing mix (7Ps).